Analysis of Tone at the Top Principle’s Implementation in Fraud Prevention on Public University in Kupang City - Bolty Evelyn Rilen Ballo; Minarni Anaci Dethan; Yohana Febiani Angi; Sarinah Joyce Margaret Rafael (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
Fraud prevention can be done by embedding fraud awareness to an entity’s employees and this actively demonstrates that management needs to create a valid control environment by creating a tone at the top to erode the hypocritical behavior of each leader at all levels. This research was conducted on public universities in Kupang City namely Universitas Nusa Cendana, Politeknik Negeri Kupang, Politeknik Kesehatan Kementerian Kesehatan Kupang, and Politeknik Pertanian Kupang. The goal of this study was to discover the impact of tone at the top principle on fraud prevention on public universities in Kupang. The sampling technique used was purposive sampling with total amount of sample was 46. All data was analyzed with SmartPLS 3.0 as the analysis tool the technique used was simple linear regression. The outcomes of this study partially show that the principle of tone at the top has a notable effect on the fraud prevention in public universities in Kupang. Meanwhile, the results of the study concurrently perform that the principle of tone at the top 43,8% affected fraud prevention while 56,2% was influenced by other factors.